Probing the effect of an inhibitor of an ATPase domain of Hsc70 on clathrin-mediated endocytosis1. Issue 10 (15th October 2015) - Cho, Hyungseoph J.; Kim, Gun-Hee; Park, Seong-Hyun; Hyun, Ji Young; Kim, Nak-Kyoon; Shin, Injae
<x xml:space="preserve">Abstract</x> Az blocks the association of Hsc70 with clathrin and consequently suppresses the disassembly of CCVs during clathrin-mediated endocytosis.